Diseño de una Planta de Producción de Leche Pasteurizada en la Parroquia de Tocachi, Provincia de Pichincha, Cantón Pedro Moncayo - Estrella Carlosama, Marco Xavier (2024)
The purpose of this research project is to propose three designs of industrial plants producing pasteurized milk based on capacities, offers and demands, with the objective of identifying the proposal that stands out based on the evaluations that will be applied to each of the models, which are developed according to the Systematic Layout Planning methodology, which is a fundamental part to ensure that the distribution and planning of the designs are correct. The idea for the development of this project arose from the need of the ASOTOCACHI association in search of alternatives to avoid economic losses caused by acidification, spills and transportation. Since this association is located in the Province of Pichincha, in the Pedro Moncayo canton, this is the macro-location, while for the micro-location, the Tocachi Parish was chosen based on the evaluations carried out. In order to know the viability of the project, a market study was carried out with the objective of recognizing a possible demand and future clients, finally a series of quotations were made to obtain an approximate monetary value of the project.